Secured obfuscated queries in spatial networks. (1st January 2013) - Priya Iyer, K.B.; Shanthi, V.
The recent drive in communication technology made smartphone users search for geographical point of interest such as nearest ATM, shopping mall and hospitals. The thirst for geo-search opens novel spatial queries in the arena of location-based apps as well as techniques that enhance the user location privacy. This paper introduces a new obfuscation technique for protecting user location based on k -means clustering. A new query called Secured Obfuscated Spatial (SOS) query to provide an analysis of the proposed obfuscation technique is developed to evaluate the efficiency. Finally, the experimental results validate the solution in preserving user privacy.